The Tacziya ecstasy as political expression - Jan Hjärpe (Scripta Instituti Donneriani Aboensis, 1982)
Ta'ziya, "consolation", has become the Shi technical term for the liturgical mourning and commemoration of the martyred Imams, particularly the ritual lamentation for the death of Husayn, celebrated formerly often in the form of passion plays in which the heart is the drama of Kerbela, but in which in addition the whole of human history is viewed sub specie Kerbelae. Nowadays the celebration is first and foremost in the form of processions (in our Western mass media called "demonstrations"), enga ing huge masses of people in emotion-evokingbehaviour, also including processions to the cemetery. For the contents of the classical Shi'i passion plays and their performance, and for the theological interpretation of the sacrifice of Husayn and the other martyrs, we refer the reader to the available literature on the subject. The Ta`ziya of Husayn falls in the month of Muharram, with its culmination on the 10th day (ruz-i katl, "the day of the murder"), the Ashara' festival, and is followed up by the mourning ceremony on the 40th day (naziarba' in) from the 'Ashura' (20th day of Safar). It is important to note the immense impact of the Ta'ziya on the emotions of the participant masses, emotions aroused by several means. We have here the suggestive sentimentality of the speeches held by the Mullas, dwelling on the tribulations and sufferings of Husayn and his family and followers, on the cruelty and baseness of his enemies, and on the courage of the 72 noble-hearted martyrs of Kerbela. In the processions, the emotions are aroused by the rhythmical repetition of formulae expressing mourning for the martyrs and hatred of their murderers. Many of the participants are dressed in shrouds, many wear chains, ropes and scourges, and the lamentations are accompanied by self-flagellation of the naked backs. People beat their breasts, some have put earth on their heads. Women weep, bewailing the pains of Husayn and the 72.